Exploring the Relationship between the Structural Characteristics and Mechanical Behavior of Multicomponent Fe-Containing Phases: Experimental Studies and First-Principles Calculations - Dongtao Wang; Xiaozu Zhang; Hiromi Nagaumi; Minghe Zhang; Pengfei Zhou; Rui Wang; Bo Zhang (Molecules, 2023)
A comprehensive understanding of the structural characteristics and mechanical behavior of Fe-containing phases is important for high-Fe-level Al-Si alloys. In this paper, the crystal characteristics, thermal stability, thermophysical properties and mechanical behavior of multicomponent α-AlFeMnSi and α-AlFeMnCrSi phases are investigated by experimental studies and first-principles calculations. The results indicate that it is easier for Fe and Cr to substitute the Mn-12j site in α-AlMnSi in thermodynamics; Cr is preferred to Fe for substituting Mn-12j/k sites due to its lower formation enthalpy after single substitutions at Mn atom sites. The α-AlFeMnCrSi phase shows higher thermal stability, modulus and intrinsic hardness and a lower volumetric thermal expansion coefficient at different temperatures due to the strong chemical bonding of Si-Fe and Si-Cr. Moreover, the α-AlFeMnCrSi phase has a higher ideal strength (10.65 GPa) and lower stacking fault energy (1.10 × 103 mJ/m2). The stacking fault energy evolution of the different Fe-containing phases is mainly attributed to the differential charge-density redistribution. The strong chemical bonds of Si-Fe, Si-Mn and Si-Cr are important factors affecting the thermophysical and mechanical behaviors of the α-AlFeMnCrSi phase.